The Effectiveness of Cough Etiquette Counseling among People with Presumptive and Confirmed Tuberculosis - Gita Sekar Prihanti; Nilam Rizki Julianto; Aditya Hendra Sasmita; Aldi Nurfahmi; Annisa Setyautami; Debby Rosyida; Tiara Muslimawaty; Nur’aini Fatmawati (Jurnal Berkala Epidemiologi, 2021)
Background: Tuberculosis (TB) is one of the most severe global health problems. The World Health Organization recommends the application of and compliance with infection control measures, one of which is cough etiquette to prevent transmission of pathogenic droplets. Purpose: The aim of the current research was to determine the effectiveness of cough etiquette counseling on changes in the knowledge, behavior, and awareness of patients with confirmed and suspected TB at Public Health Center (PHC) of C in K city. Methods: This research was designed as a pre-experimental study and was conducted in July 2018. The target population of the research comprised TB patients who were being treated in PHC of C in K city. The inclusion criteria were patients at PHC of C in K city with confirmed TB recorded between January and June 2018 and those with suspected TB reported between May and June 2018. This research was analyze based on univariable and bivariable analysis using T-testing and Wilcoxon testing. Results: There were significant differences in knowledge changes before and after cough etiquette counseling (mean difference = 3.72; p < 0.00). There was a significant difference in behavior before and after counseling (mean difference = 1.12; p = 0.04). There was also a significant difference in awareness before and after counseling (mean difference = 5.89; p < 0.00). Conclusion: Changes in knowledge, behavior, and awareness were observed in confirmed and suspected TB patients after cough etiquette counseling.